Towards the dispersion relations for dielectric optical fibers with helical windings under slow- and fast-wave considerations - A comparative analysis - Kumar D.; Choudhury P.K.; Singh II O.N. (My University, 2025)
The paper presents the electromagnetic (EM) wave propagation in cylindrical optical fibers with helical windings under slow- and fast-wave considerations. Field components are deduced for both the cases, and also, the dispersion relations are obtained by applying the boundary conditions, as modified by the presence of conducting helical windings. Two special cases are considered corresponding to the values of the helical pitch angle as 0° and 90°. A comparison of the dispersion relations is presented.